Parasite helminthes, class cestode, diagnosed by hooklets on FNAC - Verma, Nidhi; Sharma, Bhavna; Singh, Chhaviraj; Sharma, S. P. (International Journal of Research in Medical Sciences, 2018)
Parasitic infestation is a common cause of morbidity in several parts of the world. Helminthes constitute a significant number of parasitic diseases, out of which large number of cases are due to cestodes. Cestodes can affect various organs, including skin, subcutaneous tissue, liver, brain, spinal cord, orbit, muscle, gastrointestinal tract and heart. Parasites are routinely diagnosed by histopathology, serology, radiology and stool examination however FNAC can also serve as low cost out-patient procedure for diagnosis of certain parasites especially in cases of sub cutaneous nodules. Subcutaneous nodule is a relatively uncommon presentation and is often misdiagnosed clinically. This study includes case series of five cases of subcutaneous parasitic infestation by cestodes that were diagnosed by FNAC. <!–[endif]–>